The Migrant Pay Gap Understanding Wage Differences Between Migrants and Nationals. - Amo-Agyei, Silas (International Labour Organisation (ILO), 2020)
This report analyses how migrant wages have evolved in 49 countries before the COVID-19 pandemic the difficulties faced by migrants in receiving the same pay as nationals. It examines gender discrimination and the difficulties migrants have in getting a job that corresponds to their level of education.